Something old, something new from cognitive load theory. (December 2020) - Ayres, Paul
Abstract: This article discusses the findings from a collection of six studies linked together by the common theme of cognitive load theory and published in Computers in Human Behavior. A number of familiar cognitive load conditions and effects are investigated in computer-based environments, namely worked examples, split-attention, and the expertise reversal effect; but in many cases cognitive load considerations are combined with other learning strategies such as pre-training, thinking aloud, self-explanations, embodied cognition, and presentation pausing . A number of key findings are identified including the use of contemporary physiological instruments to measure cognitive load. There is also a focus on real-world tasks and medical education, as well as the self-management of cognitive load.